PENDEKATAN SOSIAL DALAM SOSIOLOGI PENDIDIKAN (MENELAH HUBUNGAN INDIVIDU, KELOMPOK DAN MASYARAKAT DISEKOLAH) - Yuni (Jurnal Salome : Multidisipliner Keilmuan, 2026)
This article discusses the application of a social approach in Educational Sociology with a focus on the relationship between individuals, groups, and society within the school environment. Schools as educational institutions not only function as places for the transfer of knowledge but also as spaces for complex social interaction. This study aims to analyze how social interactions are formed and influence the behavior and development of students in an educational context. The method used is a qualitative approach with literature study techniques and descriptive analysis of various social phenomena in schools. The study results show that harmonious relationships between individuals, groups, and society play an important role in creating a conducive learning environment, shaping students' character, and increasing the effectiveness of the learning process. On the contrary, disharmony in social interactions can lead to various problems such as conflict, lack of cooperation, and low learning motivation. Therefore, a social approach in education becomes very important to implement in order to build positive and sustainable interactions in the school environment.